Pengelolaan sampah: tantangan dan solusi untuk lingkungan - Islamiyah, Nur (Maliki Interdisciplinary Journal, 2025)
Waste management is a critical environmental issue that is becoming increasingly urgent worldwide, including in Indonesia. The rising volume of waste, coupled with inadequate management systems, has led to various problems, such as environmental pollution, negative health impacts, and ecosystem damage. This paper aims to identify the main challenges in waste management and propose solutions to mitigate its adverse effects. The challenges in waste management in Indonesia include increasing waste volume, lack of infrastructure, low public awareness, and significant environmental impacts. Solutions presented in this paper include waste reduction at the source, the implementation of waste-to-energy technologies, and public education and awareness campaigns on responsible waste management. Furthermore, the role of the government in policy-making, as well as collaboration between the private sector and society, is crucial to creating a sustainable waste management system. It is hoped that the application of these solutions will result in more effective waste management and have a positive impact on the environment.